Employee Commitment: A Back and Moving Forward - Meyer, John (Edward Elgar Publishing, 2016)
Admittedly, this poses a challenge to researchers hoping to compare commitment across national boundaries (that is, does one use the traditional or evolving culture as the ... Of course there are many Looking back and moving forward 523.